The Winding Paths of Russian Imperial Politics: On Die Geburt des russländischen Imperiums: Herrschaftskonzepte und -praktiken im 18. Jahrhundert by Ricarda Vulpius - Kosińska, Urszula (Kwartalnik Historyczny, 2022)
The article discusses the book Die Geburt des russländischen Imperiums by Ricarda Vulpius, a publication that tracks the emergence of the conceptual background for governing the growing Russian Empire in the eighteenth century, when territorial gains rendered the country increasingly multinational, multi-faith and multicultural. In this paper, the book was treated as an inspiration for examining the relationship between the practices employed by Russia on newly acquired territories in the east and south of Asia, described by Vulpius in the book, and the Russian Empire’s policy towards Poland.